2019
DOI: 10.1108/mip-04-2018-0130
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of consumers’ engagement with brand-related content on social media

Abstract: Purpose The purpose of this paper is to investigate the effect of brand’s social media marketing efforts and individual’s online social interaction propensity on various levels of consumers’ engagement with brand-related social media content. Additionally, the subsequent effects of consumers’ engagement with brand-related social media content on overall brand equity and purchase intention have also been examined. Design/methodology/approach Preliminary studies were conducted to identify brands for the main s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 47 publications
5
81
0
Order By: Relevance
“…Thus, it is concluded that perceived value is a good mediator in the Chinese apparel market. The findings of this study are parallel to the previous research that tested the role of SMMAs and the mediating effect of perceived value on different brands' customer responses (Prebensen & Xie, 2017;Gan & Wang, 2017;Mishra, 2019;Chen & Lin, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, it is concluded that perceived value is a good mediator in the Chinese apparel market. The findings of this study are parallel to the previous research that tested the role of SMMAs and the mediating effect of perceived value on different brands' customer responses (Prebensen & Xie, 2017;Gan & Wang, 2017;Mishra, 2019;Chen & Lin, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Creating behaviour is where "users initiate unprompted, positive, and active contributions to social media communities" (Dolan et al, 2019(Dolan et al, , p.2217 It acknowledges that many people create and publish their content (e.g., videos, pictures, blogs, personal home pages) on online platforms (Shao, 2009) that has a positive impact on purchase decisions (Mishra, 2019).…”
Section: Creating Brand-related Contentmentioning
confidence: 99%
“…It is considered as a well-known and highly valid theory because its principles are generally accepted and can be applied in many situations (Liu, North, & Li, 2017;Plume & Slade, 2018). UGT is a comprehensive framework that identifies consumers' motivations and has evolved over the years (Hossain, 2019;Mishra, 2019;Zong, Yang, & Bao, 2019).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%